2013
DOI: 10.1016/j.gloplacha.2012.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Statistical downscaling and bias correction of climate model outputs for climate change impact assessment in the U.S. northeast

Abstract: Statistical downscaling can be used to efficiently downscale a large number of General Circulation Model (GCM) outputs to a fine temporal and spatial scale. To facilitate regional impact assessments, this study statistically downscales (to 1∕8°spatial resolution) and corrects the bias of daily maximum and minimum temperature and daily precipitation data from six GCMs and four Regional Climate Models (RCMs) for the northeast United States (US) using the Statistical Downscaling and Bias Correction (SDBC) approac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
107
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 210 publications
(118 citation statements)
references
References 37 publications
4
107
0
Order By: Relevance
“…For example, Abatzoglou and Brown (2012), Stoner et al (2013), Ahmed et al (2013) each applied quantile mapping to daily climate model data that had been interpolated to a high-resolution observational grid. However, Maraun (2013) and Gutmann et al (2014) demonstrated that this approach-applying a univariate bias correction algorithm to interpolated climate data at individual grid points-can lead to fields with unrealistic spatial structure, especially if the variable being downscaled operates on spatial scales that are substantially finer than the climate model grid.…”
Section: Spatial Precipitation Examplementioning
confidence: 99%
See 1 more Smart Citation
“…For example, Abatzoglou and Brown (2012), Stoner et al (2013), Ahmed et al (2013) each applied quantile mapping to daily climate model data that had been interpolated to a high-resolution observational grid. However, Maraun (2013) and Gutmann et al (2014) demonstrated that this approach-applying a univariate bias correction algorithm to interpolated climate data at individual grid points-can lead to fields with unrealistic spatial structure, especially if the variable being downscaled operates on spatial scales that are substantially finer than the climate model grid.…”
Section: Spatial Precipitation Examplementioning
confidence: 99%
“…In all cases, the first half of the record is used for calibration and the second half is used as for out-of-sample verification; all reported statistics are from the verification period. Results from MBCn are compared with those from univariate QDM (e.g., as in Abatzoglou andBrown 2012, Stoner et al 2013;Ahmed et al 2013), as well as MBCp, and MBCr. For the three multivariate algorithms, all 25 grid points are corrected simultaneously, whereas QDM is applied to each grid point in turn.…”
Section: Spatial Precipitation Examplementioning
confidence: 99%
“…GCM or RCM outputs are generally biased (Ahmed et al, 2013;Teutschbein and Seibert, 2012;Mehrotra and Sharma, 2012) and there is a need to correct these outputs before they are used for regional impact studies. The RCM outputs used in this study are based on the work done by Gao et al (2013).…”
Section: Simulated Meteorological Variables From the Rcmmentioning
confidence: 99%
“…This regression model corrects systematic local effects (e.g., whether a rain gauge is positioned on the lee or windward side of a mountain). It also adds random (unexplained) small-scale variability, in contrast to approaches of combined methods that employ spatial interpolation for downscaling (Wood and Maurer, 2002;Wood et al, 2004;Payne et al, 2004) or rescale the grid-scale precipitation with a factor to match the observations (Ahmed et al, 2013). We calibrate the probabilistic regression model Figure 1.…”
Section: General Conceptmentioning
confidence: 99%